Power, crime and deadly deception - Whyte, David (Demystifying power, crime and social harm, 2023)
This chapter highlights one aspect of the contribution made by Steven Box’s Power, Crime and Mystification (PCM) to the study of corporate and white-collar crime: his use of deviance theory to illuminate the criminal subculture of corporate executives. It does so for two reasons. First, to recognise, and pay some attention to, the influence that this work has had on critical criminology, and particularly on those who have studied and written about corporate crime since the publication of PCM.